An Enzyme-Based Interdigitated Electrode-Type Biosensor for Detecting Low Concentrations of H2O2 Vapor/Aerosol - Farnoosh Vahidpour; Yousef Alghazali; Sevilay Akca; Gregor Hommes; Michael J. Schöning (Chemosensors, 2022)
This work introduces a novel method for the detection of H2O2 vapor/aerosol of low concentrations, which is mainly applied in the sterilization of equipment in medical industry. Interdigitated electrode (IDE) structures have been fabricated by means of microfabrication techniques. A differential setup of IDEs was prepared, containing an active sensor element (active IDE) and a passive sensor element (passive IDE), where the former was immobilized with an enzymatic membrane of horseradish peroxidase that is selective towards H2O2. Changes in the IDEs’ capacitance values (active sensor element versus passive sensor element) under H2O2 vapor/aerosol atmosphere proved the detection in the concentration range up to 630 ppm with a fast response time (<60 s). The influence of relative humidity was also tested with regard to the sensor signal, showing no cross-sensitivity. The repeatability assessment of the IDE biosensors confirmed their stable capacitive signal in eight subsequent cycles of exposure to H2O2 vapor/aerosol. Room-temperature detection of H2O2 vapor/aerosol with such miniaturized biosensors will allow a future three-dimensional, flexible mapping of aseptic chambers and help to evaluate sterilization assurance in medical industry.